Surgical Site Infections in a Tertiary Referral Obstetric and Gynecologic Clinic Center in Istanbul and Review of the Literature - Celik, Hale Goksever; Celik, Engin; Dikmen, Selin; Konal, Merve; Gedikbasi, Ali (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: The present study aimed to define characteristics of the patients who were readmitted with the diagnosis of surgical site infections after gynecologic or obstetric procedures and management of these patients. We also reviewed the literature in this context. Study design: We examined 120 patients with surgical site infections that had been hospitalized and managed medically and/or surgically between April 2014 and April 2015. Characteristics of the patients were recorded and analyzed. Results: The mean age of the patients was 33.4±11.8 years. The patients were readmitted for surgical site infections on the mean of 9.6±5.4 days after the first operation. The most frequent procedures resulted with SSI were cesarean delivery, abdominal hysterectomy and vaginal birth. When patients were compared according to these procedures, there were statistically significant differences regarding age, gravida, parity, preoperative white blood cell count, postoperative white blood cell count and antibiotics usage. Conclusion: Combining evidence-based surgical site infections prevention practices and clinician and patient cooperation will result in reduction in surgical site infections incidence following obstetric and gynecologic procedures. Because of economic burden and threat to the physical and psychological health of the patients, these modifiable risks should be recognized and surgical site infections should be minimized. After surgical site infections occurred, diagnosis and proper management with antibiotics and wound care with debridement and secondary suturing is important.